PATH-30. TARGETED THERAPIES FOR PEDIATRIC LOW-GRADE GLIOMAS: A CASE SERIES. (11th November 2019) - Shah, Nidhi; Walter, Andrew; Kaur, Gurcharanjeet
Abstract: Pediatric central nervous system (CNS) malignancies are the most common malignancies of childhood. The standard treatment plan for most CNS malignancies involves surgery, chemotherapy, radiation, and/or a combination of above therapies. Unresectable symptomatic low grade gliomas, such as pilocytic astrocytomas and gangliogliomas, are slow growing tumors that are typically responsive to a single course of intravenous chemotherapy, but in select patients these WHO grade I or II tumors can recur and be refractory to multiple courses. Molecular diagnostics can offer valuable insight into the tumor microenvironment, where targeted therapies can be offered for specific actionable mutations. Here we report a case series of 3 pediatric patients, with unique CNS malignancies, currently on targeted therapies for tumor-specific somatic mutations. Patient A is a 5 year old male with unresectable Neurofibromatosis-1 related plexiform neurofibroma of the nasopharyngeal space as well as optic pathway glioma, with a mutation of the MAPK/ERK pathway. Patient B is a 6 year old male with recurrent, refractory pilocytic astrocytoma of the optic pathway and hypothalamus, with progression through several courses of intravenous chemotherapy, noted to have somatic NACC2-NTRK mutation. Patient C is a 17 year old female with unresectable, pontomedullary ganglioglioma, noted to have BRAF-V600E mutation. Patient A is treated with Selumetinib, for about 6 months, with near resolution of nasopharyngeal mass. Patient B is treated with Larotrectinib, for about 3 months, with stability of clinical symptoms. Patient C is treated with Vemurafenib, for about 10 months, with stability of lesion size and patient-reported clinical improvement. No adverse events were noted for any of these patients and all medications were administered orally. Significant improvement in quality of life was reported, as they did not have central lines or bone marrow suppression. Targeted inhibitors provide a reasonable treatment option for relapsed, refractory CNS malignancies with actionable mutations.